Absenteeism and presenteeism in healthcare workers due to respiratory illness. (26th March 2021) - Kuster, Stefan P.; Böni, Jürg; Kouyos, Roger D.; Huber, Michael; Schmutz, Stefan; Shah, Cyril; Bischoff-Ferrari, Heike A.; Distler, Oliver; Battegay, Edouard; Giovanoli, Pietro; Guckenberger, Matthias; Kohler, Malcolm; et al.
Abstract: Objective: To assess influenza symptoms, adherence to mask use recommendations, absenteesm and presenteeism in acute care healthcare workers (HCWs) during influenza epidemics. Methods: The TransFLUas influenza transmission study in acute healthcare prospectively followed HCWs prospectively over 2 consecutive influenza seasons. Symptom diaries asking for respiratory symptoms and adherence with mask use recommendations were recorded on a daily basis, and study participants provided midturbinate nasal swabs for influenza testing. Results: In total, 152 HCWs (65.8% nurses and 13.2% physicians) were included: 89.1% of study participants reported at least 1 influenza symptom during their study season and 77.8% suffered from respiratory symptoms. Also, 28.3% of HCW missed at least 1 working day during the study period: 82.6% of these days were missed because of symptoms of influenza illness. Of all participating HCWs, 67.9% worked with symptoms of influenza infection on 8.8% of study days. On 0.3% of study days, symptomatic HCWs were shedding influenza virus while at work. Among HCWs with respiratory symptoms, 74.1% adhered to the policy to wear a mask at work on 59.1% of days with respiratory symptoms. Conclusions: Respiratory disease is frequent among HCWs and imposes a significant economic burden on hospitals due to the number of working days lost. Presenteesm with respiratory illness, including influenza, is also frequent and poses a risk for patients and staff. Trial registration: NCT02478905 (clinicaltrials.gov )